How we tackled the problem of assessing humanities, social and behavioural sciences in medical education. (1st February 2016) - Goodwin, Dawn; Machin, Laura
Abstract: Background: Assessment serves as an important motivation for learning. However, multiple choice and short answer question formats are often considered unsatisfactory for assessment of medical humanities, and the social and behavioural sciences. Little consensus exists as to what might constitute 'best' assessment practice. What we did: We designed an assessment format closely aligned to the curricular approach of problem-based learning which allows for greater assessment of students' understanding, depth of knowledge and interpretation, rather than recall of rote learning. Conclusion: The educational impact of scenario-based assessment has been profound. Students reported changing their approach to PBL, independent learning and exam preparation by taking a less reductionist, more interpretative approach to the topics studied.